Horizons : 14 Polish contemporary artists. - Bang, Sang-hoon; Cieslinska, Nowojka; Deecke, Thomas; Gorczyca, Lukasz; Herbert, Simon; Kepinska, Alicja; Kim, Sun Jung; Morzuch, Maria; Prasal, Aneta; Robakowski, Jozef; Rose, Barbara; Rypson, Piotr; et al. (Kyongju : Sonje Museum of Contemporary Art, 1996)
Abakanowicz, Magdalena ; Balka, Miroslaw ; Chlanda, Marek ; Ciecierski, Tomasz ; Deskur, Marta ; Gustowska, Izabella ; Krasinski, Edward ; Kruk, Mariusz ; Kulik, Zofia ; Opalka, Roman ; Robakowski, Jozef ; Szewczyk, Andrzei ; Tarasewicz, Leon ; Wodiczko, Krzysztof
biografie
Horizons : 14 Polish contemporary artists, Sonje Museum of Contemporary Art, Kyongju, August 10 - October 6 1996 ; Kwangju Museum of Contemporary Art, Kwangju, October 16 - November 25 1996 ; Chosun Ilbo Gallery, Seoul, February 15 - March 2 1997
Engels
boek
Keywords: Polen